Strategi promosi di UMKM Stronger Manufacture - Tessar Fabiansyah; Hadisantono (Universitas Atma Jaya Yogyakarta, 2023)
MSME Stronger Manufacture is a business that produces t-shirts, jackets, corsa, sweaters, jerseys, and others. The main product is t-shirts. The main problem that occurred was the decline in sales over the last six months by 18%. From the sales results, calculations were carried out using BCG (Boston Consulting Group) Matrix analysis which demonstrates the business position in question mark quadrant and the root cause of the problem was the need for information to consumers. Furthermore, by using PLC (Product Life Cycle) analysis, the preferred problem to be solved was Promotion. By discussions with the stakeholder, alternative solutions were obtained, namely improving factors in the marketing mix (product, promotion, price, place). After various analyses and discussions with the stakeholder, the Promotion was selected. Promotion was done by designing a promotional strategy and content calendar using social media. The implementation was carried out on July 3 – 8, 2023 on the Instagram of MSMEs Stronger Manufacture. Furthermore, the implementation results demonstrated an increase in engagement by 2.338%.